TURN-TAKING STRATEGIES USED IN A NEW ZEALAND RADIO INTERVIEW PROGRAMME AND PEDAGOGICAL IMPLICATIONS IN LANGUAGE CLASSROOMS - Hong Phuong, Cao Thi; Tho, Pham Xuan (VNU Journal of Foreign Studies, 2020)
The present paper analyses conversational strategies employed by the interviewer on a New Zealand radio programme from conversation analysis (CA) perspective. This study employs a documentary method of interpretation in order to seek answer(s) to the research question. Specifically, Sacks, Schegloff and Jefferson’s (1974) model of conversation analysis was adopted to explore turn-taking strategies used in the interview. The analysis reveals that the interviewer employed a variety of turn-taking strategies such as signaling the end of turn, holding a turn, asking a question, self-selection and “prosodic features” (ibid.) to achieve the purpose of the interview. The findings of this study suggest several potential CA-informed pedagogical implications for English language teaching classroom.